Identifikasi Telur Nematoda Usus Golongan Soil Transmitted Helminth (STH) Pada Kuku Petani - Arisanti, Dewi; Widyanti, Tuty; Fatmawati, Andi; Rustiah, Waode; Anita, Anita; Rosmawati, Andi (Lembaga Penelitian dan Pengabdian Masyarakat Politeknik Muhammadiyah Makassar, 2023)
A farmer is someone who works in agriculture and is in direct contact with the soil every day without using personal protective equipment. Some farmers also use organic fertilizer as an additional fertilizer to fertilize plants. Coupled with personal hygiene and low environmental sanitation, these things are factors that cause infection with soil-transmitted helminth worms. The purpose of this study was to identify the eggs of intestinal nematodes of the STH class on the nails of farmers. This research was conducted by laboratory observation using the flotation research method. The object of this research is the nails of farmers in Kampuno Village, Barebbo District, Bone Regency, with 30 samples. The results of the research conducted were that 2 samples (6.67%) were positive for STH worm eggs, namely hookworm, and 28 samples (93.3%) were negative; no STH worm eggs were found. So, it can be concluded that two samples of intestinal nematodes of the STH group were found on the nails of farmers.